IDENTIFIKASI DAN KELIMPAHAN PLANKTON DI PULAU MAMBURIT KABUPATEN SUMENEP - Sawiya Sawiya; Diana Afiati; Guntur Guntur; Ummi Zakiya (Fakultas Pertanian Universitas Yudharta Pasuruan, 2018)
Plankton is an organism, most of them live hovering and floating in the water with limited movement wich most of them live hovering and floating in the water with limited movement where the stream brings. Plankton has an important role for other organisms, especially in the sea because plankton is a primary producer wich is a food-produser organism. Plankton has never been identified on Mamburit Island, the purpose of this study is to find out how many species were found on Mamburit Island in each of the windward 1 and windward II locations, leeward 1 leeward II twice replication. The results obtained that phytoplankton and zooplankton replication 1 at location of windward 1 and windward II did not have plankton, leeward 1 was found only 1 species of Synedra flugens, 13.32 ind/liter, on location and leeward II, found 2 species, Pleurosigma, and Synedra flugens such as 2 species 19.98 ind / liter, while in replication 2 found 4 species of Synedra Flugens, Pleurosigma, Rhizosolenia borealis, Nauplius,with the number of windward I was 99.96 ind/liter, Leeward 1 was found 1 species, Rhizosolenia borealis, with a total of 6.66 ind / liter. Windward II was not found at all, and leeward II was found in 2 species of Synedra Flugens, Nitzschia with a total of 13.32 ind / liter.